1997
DOI: 10.1046/j.1365-2958.1997.4851839.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of cis‐acting sequence and structural elements required for antitermination of the Bacillus subtilis tyrS gene

Abstract: SummaryThe Bacillus subtilis tyrS gene belongs to the T box family of aminoacyl-tRNA synthetase and amino acid biosynthesis genes, which are regulated by a common mechanism of transcriptional antitermination. Each gene is induced by specific amino acid limitation; the uncharged cognate tRNA is the effector inducing transcription of the full-length message. The leader regions of the genes in this family share a number of conserved primary sequence and secondary structural elements, the functions of which are un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(111 citation statements)
references
References 27 publications
6
105
0
Order By: Relevance
“…For example, a single species of tRNA Tyr , with an anticodon to match the UAC tyrS specifier, has been identified; this tRNA must translate UAU tyrosine codons, by wobble pairing, yet a UAU specifier sequence mutation results in a severe decrease in tyrS readthrough (30). In contrast, no variant of tRNA Val with the appropriate anticodon has been reported, yet the switch to a valine specifier was successful.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a single species of tRNA Tyr , with an anticodon to match the UAC tyrS specifier, has been identified; this tRNA must translate UAU tyrosine codons, by wobble pairing, yet a UAU specifier sequence mutation results in a severe decrease in tyrS readthrough (30). In contrast, no variant of tRNA Val with the appropriate anticodon has been reported, yet the switch to a valine specifier was successful.…”
Section: Discussionmentioning
confidence: 99%
“…These features include the capacity of the leader RNA to form alternative secondary structures, one of which can serve as an intrinsic transcription terminator or as an anti-SD (ASD) helix that pairs with an SD sequence, blocking translation initiation. The major structures formed within the T-box RNA, in addition to the segments that can form the terminator/antiterminator (or ASD/anti-ASD) elements, are designated stem I, stem II, the stem IIA/stem IIB pseudoknot, and stem III (47,88) (Fig. 1A).…”
Section: General Features Of T-box Riboswitch Rnamentioning
confidence: 99%
“…T-box leader RNAs are further characterized by the existence of a set of conserved primary sequence elements at specific locations relative to the structural features (43). Mutational studies have demonstrated that many of the sequence and structural features conserved in T-box leader RNAs are important for function (49,88,112), but overall primary sequence conservation is low. Interestingly, the two main features of tRNAs (the anticodon and the base immediately preceding the CCA at its 3Ј end) that are recognized by the T-box RNAs are also usually central elements for recognition by the cognate aaRS (14).…”
Section: General Features Of T-box Riboswitch Rnamentioning
confidence: 99%
“…Both structures displayed the codon within the Specifier loop. However, the second most stable structure with a free energy (DG°at 298°K) of ÿ19.2 Kcal/mol most closely resembled the conformation supported by genetic analysis in vivo and chemical and enzymatic probing experiments in vitro (Rollins et al 1997;Winkler et al 2001;Putzer et al 2002;Yousef et al 2005). The other structure was only modestly more stable with a DG°of ÿ21.0 Kcal/mol.…”
Section: Monitoring Of Specifier/common Complex Formation By Spectrofmentioning
confidence: 80%